Development of a Supporting Model for Private Basic Education Institutions - Pataraprasit, Wanicha (Scholar: Human Sciences, 2014)
This research aimed to present the states and problems of supporting private basic education Institutions from the government and to develop a proposed model for supporting private basic education institutions in Thailand. The research methodology compromised in 5 steps. 1st Step: Documentary analysis to develop a research framework. 2nd Step: Documentary analysis and survey research about the states and problems of supporting private basic education Institutions. 3rd Step: Construct the proposed model. 4th Step: Evaluate propriety and feasibility of the model by expert judgments. 5th Step: Adjust and scrutinize the proposed model. The research findings are summarized as follow: The governmental supports to private institutions are not equal to public institutions that bring to oligopoly market and unfair competitions. The study of the states of supporting private basic education Institutions finds that the government supported at the low level all, vice versa the government should support at highest all in the statistic significant different of 0.05. The important problems are the supporting in the investment expenditures and academic supports. The proposed model for Supporting Private Basic Education Institutions is "The Integrative Model" which comprises of 2 components (1) The integration of Demand-size financing and Supply-side financing (2) The integration of In Cash and In Kind supports. Demand-size financing consists of education coupon and health promotion for students. Supply-side financing is the infrastructure developing funds, teachers‘ salary coupon, teachers‘ welfare, the academic funds for teacher and the honor award for institutes, the school executive and teacher. Research Suggestion: The next should be a research for the Strategies of Supporting Private Basic Education Institutions to find out the key success factors.